"Could you please repeat that?" Speech design best practices for minimizing errors. (September 2018) - Hess, Alyssa S.; Zellman, Jenny
Until recently, designing the interactions between systems and users has relied primarily on visual communication. However, with the dramatic increase in the use of virtual assistants, voice interaction design is now a sought after skill for human factors and user experience practitioners. In this practice-oriented paper, we aim to identify the best practices for dialog designers striving to minimize errors in communication between the user and the voice-enabled system. Furthermore, we highlight the technology behind voice systems as well as the importance of minimizing errors when our voice-controlled devices become a part of highly sensitive interactions: specifically, when accessing critical, private information. Summary: This is a practice-oriented paper highlighting six best practices for avoiding errors when designing voice-enabled systems. Errors in voice systems have been found to require a great deal of user effort to resolve, as well as strongly influence user satisfaction with their voice system. We discuss the technical foundation for voice user interfaces (VUIs) as well as the evolving nature of these systems. The purpose of this paper is to aid and inform upcoming voice design practitioners in the best method for dialog designing.